Đọc hiểu và các kỹ năng đọc hiểu tiếng Anh = College reading skills : Advanced level : a programmed self-study course - Blake, Kathryn A.; Phạm Thu Hằng (Tp.HCM : Thanh niên, 2003)
Reading skills; Tests - Examinations.
Keywords: Tiếng Anh; Reading; Reading (college).; Reading skills